PENYUNTINGAN PADANAN KATA BUKU TEMATIK TERPADU KURIKULUM 2013 EDISI REVISI 2017 UNTUK SISWA SD/MI KELAS 1 BERBAHASA ANGKOLA-MANDAILING - Toras Barita Bayo Angin; Hasian Romadon Tanjung (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to describe the equivalent in integrated thematic book of Angkola - Mandailing language. The research was conducted for two months (June – July 2021) in Institut Pendidikan Tapanuli Selatan and the approach of the research used descriptive qualitative. Object of the research is integrated thematic book at the first grade students of elementary school, 2017 edition revised 2013. The data of the research includes words and sentence in Indonesian thematic textbooks, Mr. Jamal Nasution. Validity of the data is the expert team from the Language Center of North Sumatra Province. The results showed that the edited equivalent of the words in the appropriate book in the Angkola-Mandailing language includes 127 words and sentences.